Tingkat Adopsi Praktik Pertanian Organik Bersertifikat pada Petani Padi di Kecamatan Rilau Ale - Sri Amaliah; Amal Said; Suardi Bakri (SENTRI: Jurnal Riset Ilmiah, 2025)
Rilau Ale District in Bulukumba Regency has agroecological conditions that support the development of organic rice, and several farmer groups have begun implementing environmentally friendly cultivation practices. Rising demand for organic rice has encouraged farmers to shift toward production systems that meet certification standards. This study aims to assess the level of adoption of certified organic farming practices among farmers, which is essential for strengthening farmer institutions and improving their capacity to consistently apply certification requirements. The study was conducted from May to July 2025 in Bontobangun, Bajiminasa, Bontoharu, and Karama Villages using qualitative descriptive analysis and a Likert scale. The findings show that adoption of organic certified practices is progressing, although not yet consistent across all stages. Farmers’ awareness is strong, supported by their understanding of organic principles and restrictions on chemical inputs. Their interest has formed through group interactions and perceived environmental benefits. At the evaluation and trial stages, farmers remain at a moderate level, indicating a need for stronger technical and administrative support. The adoption stage has begun to appear but lacks stability due to limited capacity, facilities, and institutional backing. Overall, adoption is in a transitional phase that requires systematic reinforcement to achieve sustainable organic farming.